Pelaksanaan Salat Jumat di Rumah Mengikuti Siaran Radio Menurut Pemikiran Syekh Ahmad Bin Siddiq Al-Ghummari - Asysyairazi Abdul Wahid (Ar-Raniry: International Journal of Islamic Studies, 2020)
The Friday prayer is fardu 'ain for every male Muslim, this has become an ijma' (agreement) without any difference of opinion among the scholars. According to most scholars, Friday prayers are carried out in congregation with an uninterrupted row of empty more than 9 people, whereas if one row of rows of shaf is empty there are less than nine people, that is fine. However, the conditions for the validity of Friday prayers such as those that must be performed in the city, with a certain number, must be carried out in a mosque and there is no mention of the implementation of Friday prayers, according to Sheikh Ahmad bin Siddiq Al-Ghummari, these conditions do not have the proof of sharia. to her. It is strengthened again by the interpretation of the meaning of ذكرالله in verse 9 of surah al-Jumuah. This word literally means "remembering Allah." However, ذكرالله in this verse according to the jumhur ulama means "Friday prayer." This opinion was rejected by Sheikh Ahmad bin Siddiq Al-ghummari, according to him the lafaz means Friday sermons, because of that, it is permissible to hear Friday sermons even though they are broadcast via broadcast. radio, not necessarily in a mosque. According to Sheikh Ahmad bin Siddiq al-Ghummari, the implementation of Friday prayers at home via radio is valid with three conditions: First, the time of its implementation is concurrent or not performed by those who participate outside the prayer time (because every prayer must be done on time). Second, the country or place of congregational prayer must be behind the country or place of prayer for the imam, because the legal requirements for congregational prayer are: the priest must be in front of the congregation. Third, the congregation must be in one place with other people, even if only one person is with him, because at least the condition for the group is only two people.